SOLUBILITY BEHAVIOR OF ALKALI ALUMINOSILICATE COMPONENTS IN AQUEOUS FLUIDS AND SILICATE MELTS AT HIGH PRESSURE AND TEMPERATURE - Mysen B.O.; Armstrong L. (My University, 2002)
The solubility behavior of K2O, Na2O, Al2O3, and SiO2 in silicate-saturated aqueous fluid and coexisting H2O-saturated silicate melts in the systems K2O-Al2O3-SiO2-H2O and Na2O-Al2O3-SiO2-H2O has been examined in the 1- to 2-GPa pressure range at 1100°C. Glasses of Na- and K-tetrasilicate compositions with 0, 3, and 6 mol% Al2O3 were used as starting materials. In both systems, the oxides dissolve incongruently in aqueous fluid and silicate melt. When recalculated to an anhydrous basis, the aqueous fluids are enriched in alkalis and depleted in silica and alumina relative to their proportions in the starting materials. The extent of incongruency is more pronounced in the Na2O-Al2O3-SiO2-H2O system than in the K2O-Al2O3-SiO2-H2O system.The partition coefficients of the oxides, Doxidefluid/melt, are linear and positive functions of the oxide concentration in the fluid for each composition. There is a slight dependence of the partition coefficients on bulk composition. No effect of pressure could be discerned. For alkali metals, the fluid/melt partition coefficients range from 0.06 to 0.8. For Al2O3 this range is 0.01 to 0.2, and for SiO2, it is 0.01 to 0.32. For all compositions, DK2Ofluid/melt~DNa2Ofluid/melt>DSiO2flui d/melt>DAl2O3fluid/melt for the same oxide concentration in the fluid. DK2Ofluid/melt, DNa2Ofluid/melt, and DSiO2fluid/melt correlate negatively with the Al2O3 content of the systems. This correlation is consistent with a solubility model of alkalis that involve associated KOH°, NaOH°, silicate, and aluminate complexes.